TINJAUAN DESAIN FORMULIR REKAM MEDIS RAWAT INAP PELAYANAN BEDAH DI RUMAH SAKIT KHUSUS BEDAH RAWAMANGUN - Indah Kristina; Dede Maysaroh (APIKES Bhumi Husada Jakarta, 2023)
ABSTRACT This research was conducted to identify SOP (standart operasional procedure) governing the design of medical record forms, analyze components reviewed from anatomical, physical and content aspects contained in surgical hospitalization forms, and identify design constraints and use of surgical hospitalization forms. The research method used is a quantitative descriptive analysis method with percentage results to obtain an overview of the design review of surgical hospitalization forms at Rawamangun Special Hospital of Surgery East Jakarta. The data collection method is carried out by direct observation using checks and interviews to respondents using interview guidelines and informed consent interviews. The results of this study showed that the hospital already has a policy related to form design, namely SPO (standard operational procedure) form renewal. Guidelines for filling out medical records files and form design policies in the medical record service guidelines, fulfillment of anatomical, physical and fill aspects on surgical hospitalization forms have not been completed 100% fulfilled, from the average physical aspect of 79.20%, anatomical aspects 47.42% and content aspects 95.7%. For design constraints, the lack of knowledge about the rules of form design according to existing policies in hospitals for usage constraints is not too many obstacles, it's just that the instructions are diformed that are less clear. In conclusion, the hospital already has policies related to the design of medical record forms both SPO and guidelines governing aspects of form design, but there are still unmet aspects of the design of surgical hospitalization forms at Rawamangun Surgical Special Hospital. Existing forms do not meet the rules of the form design policy that has been created by the hospital. Bibliography: 14(2012 – 2021) Keywords: Review, Design, Form, SOP.